A legal analysis pertaining to statutory employment rights and protection in the workplace - Hapriza Binti Ashari (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2013)
The primary objective ol this study is to examine precisely the working of scb:tcd provisions of the Employment Act 1955, primarily focusing on the legislated employees' rights al the workplace governing wages, hours of work, rest day, public holidays, annual leave, sick leave and maternity protection. Legalistic method of identifying legal problems was performed lo accomplish the primary objective of the research. This method involved the process of identifying the legal issues, selection of the rule of Jaw that governs the issues, application of the Jaw to the facts and formulation of conclusions of law. In conducting the legal analysis, reterences were made to both primary and secondary legal authorities. The primary legal authorities covered legislative sources, executive sources and judicial sources whilst the secondary legal authorities involved a wide range of materials such as law reports, academic law journals, digests and law books. The comprehensive legal analysis provided a critical insight into the exact meaning, correct interpretation and right application of the Jaw that prescribe the statutory rights at the workplace. The analysis and findings are discussed thoroughly under separate topics and presented systematically in chapter three lo chapter nine of the thesis. These chapters also discussed the lacunas in the law and recommended a series of measures that address some aspects of employees' rights which aim to provide some improvement to the legal document. The study also measures the levels of basic knowledge of these rights among HR practitioners, the provision of Jaw which is the greatest concern to them; the key sources utilised for obtaining advice and their level of concern in making legally sound decisions. It also attempts to identify the difference in the levels of knowledge across the demographic characteristics of the respondents; and examine the relationship between the levels of knowledge and the size of companies; and the levels of concern in making legal decision, respectively. The level of basic knowledge was measured by calculating the mean score of the variables. The data concerning the demographic characteristics, the provision of law of greatest concern, the sources of legal knowledge and the level of concern in making legal decisions were analysed using descriptive statistics and presented using frequency distributions and percentages. Kruskal-Wallis Test was used to compare mean differences in knowledge levels across age, education, tenure groups and size of companies. Spearman Correlation analysis was utilised to examine the nature of the relationship between knowledge scores and the size of companies as well as the level of concern in making legal decisions. The results reveal that the respondents possessed a moderate level of basic knowledge concerning statutory employment rights. The most important source of advice was via the Department of Labour followed via lawyers and colleagues. Statutory rights to wages were reported as the main concern followed by working time and rest breaks provision. Majority of the respondents were concerned, to some degree, about their ability in making legally sound decisions. There was no significant difference in knowledge levels across the ditlerent age, education and tenure groups; but there was a statistically significant difference in the knowledge levels across different size of companies. There was a strong, positive correlation hctween the levels of knowledge and size of companies; and a moderate positive significant correlation with the level of concern in making legal decisions.